Retro fashion: did onychophorans abandon ovoviviparity and revert to laying eggs? - Barquero-González, Pablo (2019)
Viviparity is so advantageous that it has evolved at least 140 times in the invertebrates, but some Australian and New Zealand onychophorans have gone back, abandoning ovoviviparity to return to laying eggs. Why? Here we propose that it is an adaptation to climatically inhospitable habitats and low food availability.